Strategi Pendidikan Nilai Islami di Perguruan Tinggi Umum - Herlina, Lenny (PALAPA, 2019)
Regardless of the definition of education, as much as that is the formulation of the goals of education, including those determined on the basis of ideology. The purpose of education itself is "the achievement of maturity", as the optimal point of development of human potential, both physical and spiritual, includes the functions of individuality, sociality, and morality, so that the integrity of the individual as an individual and community member is achieved. morality, and to achieve the potential value of morality in everyday life requires understanding and various efforts that are not small and require a long time. The University as an Educational Institution is certainly an important part as a forum for the formation of good values. And this paper focuses on how the efforts of the University of Mataram Medical Faculty embed Islamic values in its environment.